2020
DOI: 10.1167/iovs.61.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR via an AAV-Delivered shRNA Tested in a Rat OIR Model as a Potential Antiangiogenic Gene Therapy

Abstract: Citation: Lee SHS, Chang H, Kim JH, et al. Inhibition of mTOR via an AAV-Delivered shRNA tested in a rat OIR model as a potential antiangiogenic gene therapy. Invest Ophthalmol Vis Sci. 2020;61(2):45. https://doi.org/10.1167/iovs.61.2.45 PURPOSE.Recent studies have shown that inhibitors of the mechanistic target of rapamycin (mTOR) play important roles in proliferating endothelial cells within the retinal vasculature. Here we explore the effects of inhibiting mTOR as a potential gene therapeutic against pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
7
9
0
Order By: Relevance
“…support our previous findings that suggested an effective reduction of neovascularization by AAV2-shmTOR in CNV and OIR models [8,20]. Retinal vascular diseases share salient and common features of retinal neovascularization.…”
Section: Accepted Articlesupporting
confidence: 90%
See 1 more Smart Citation
“…support our previous findings that suggested an effective reduction of neovascularization by AAV2-shmTOR in CNV and OIR models [8,20]. Retinal vascular diseases share salient and common features of retinal neovascularization.…”
Section: Accepted Articlesupporting
confidence: 90%
“…In our previous studies, we demonstrated that inhibition of the mTOR signaling pathway using a small‐hairpin RNA (shRNA) delivered via recombinant adeno‐associated virus 2 (AAV2) (termed rAAV2‐shmTOR‐SD, renamed here as AAV2‐shmTOR) led to an effective reduction of neovascularization in the mouse choroidal neovascularization (CNV) and rat oxygen‐induced retinopathy (OIR) models [ 18 , 19 , 20 ]. In those results, we confirmed the successful transduction of AAV pseudotyped with serotype AAV2 on the retinal tissues.…”
mentioning
confidence: 99%
“…In a rat model of hVEGF, suprachoroidal injection of RGX-314 between the sclera and choroid suppressed VEGF-induced vascular leakage and vasodilation [27]. Oxygen-induced retinopathy in rat, laser induced CNV in mouse AAV2 intravitreal mTOR shRNA, wet AMD, ROP, DR [75][76][77] Laser induced CNV in mouse scAAV2 subretinal endostatin wet AMD [78] Oxygen-induced retinopathy in rat, laser induced CNV in mouse scAAV2 intravitreal, subretinal calreticulin anti-angiogenic domain (CAD) wet AMD, DR [79] Oxygen-induced retinopathy in mouse rAAV intravitreal Kringle1 domain of hepatocyte growth factor (HGFK1) wet AMD, DR [80] Oxygen-induced retinopathy in mouse Adenovirus GV120 intravitreal Galetin-1-RNAinterference ROP [81] Laser induced CNV and oxygen-induced retinopathy in mouse, AAV1-CRISPR/Cas9 intravitreal CRISPR/Cas9 targeted to VEGFR 2 wet AMD, ROP [82] Laser induced CNV in mouse AAV9-CRISPR-LbCpf1 intravitreal CRISPR-LbCpf1 targeted to VEGF A and HIF1α wet AMD [83] Laser induced CNV in mouse Lentivirus subretinal microRNAs targeting VEGF-A wet AMD [62] Laser induced CNV in mouse AAV5 subretinal PEDF, multiple miRNAs targeting the VEGFA gene wet AMD [84] Corneal chemical burn in a rabbit AAV8/9 chimeric capsid (8G9) corneal intrastromal codon optimized human leucocyte antigen G1+ G5 Corneal neovascularization [85] Oxygen-induced retinopathy in rat Lentivirus subretinal shRNAs to VEGFR2 or STAT3 ROP [86] Oxygen-induced retinopathy in rat Lentivirus subretinal VEGF-A or VEGF-A164 shRNA ROP [87] AAV = adeno-associated virus, ADV = adenovirus, AMD = age-related macular degeneration, CNV = choroidal neovascularization, DR = diabetic retinopathy, LV = lentivirus, ROP = retinopathy of prematurity.…”
Section: Vegf-blocking Agentsmentioning
confidence: 99%
“…Recombinant AAV derived from self-complementary AAV2, expressing a short hairpin RNA, blocks the activity of mTOR complexes 1 and −2. Intravitreal injection of AAV-mTOR shRNA was shown to suppress angiogenesis and inflammation in a laser-induced CNV mouse model [ 75 ] and reduce neovascularization in a rat oxygen-induced retinopathy (OIR) model [ 76 ]. In another study, the optimal viral genome size for efficient AAV assembly was ensured by using a stuffer DNA derived from the 3’ UTR of the human UBE3A gene [ 77 ].…”
Section: Preclinical Anti-angiogenic Studiesmentioning
confidence: 99%
“…Recombinant AAV derived from self-complementary AAV2, expressing a short hairpin RNA blocks the activity of mTOR complexes 1 and -2. Intravitreal injection of AAV-mTOR shRNA was shown to suppress angiogenesis and inflammation in laser induced CNV mouse model [52] and reduce neovascularization in rat oxygen-induced retinopathy (OIR) model [53]. In other study optimal viral genome size for efficient AAV assembly was ensured by using a stuffer DNA derived from 3` UTR of the human UBE3A gene [54].…”
Section: Other Pro-angiogenic Factorsmentioning
confidence: 99%